IN-VITRO REGENERATION OF MULTIPLE SHOOTS FROM APICAL MERISTEMS OF COWPEA (Vigna unguiculata L. (WALP) USING DIFFERENT GENOTYPES (LOCAL AND IMPROVED) AND MEDIA COMPOSITIONS (FUDMA JOURNAL OF SCIENCES, 2022)
Organogenesis in-vitro was evaluated in explants derived from shoot apices of four cowpea varieties cultured on Murashige and Skoog (MS) basal medium. To evaluate the response of the cowpea genotypes to in vitro regeneration, seedlings were drived from zygotic embryos excised from surface sterilized seeds after two weeks of culture on MS basal medium + vitamins supplement with 30% sucrose. To regenerate multiple shoots, apices of the in vitro seedlings with average length of 1cm were excised and cultured on MS supplemented with 0.5, 1.0 or 1.5mg/L 6-Benzylamino purine(BAP) with or without 0.1mg/L  Î±-naphthaleneacetic acid (NAA) for six weeks.  The highest shoot number was recorded with IT99k-573-2-1 and Danilla and shoot length was highest in  Kanannado, IT04k-33-2-1and Danilla indicating that Danilla responded well to in vitro regeneration.  To optimise the production of multiple shoots  the effects of different concentratios (0.5, 1.0 and 1.5mg/L) of 6-benzyaminopurine (BAP) with or without 0.1mg/L Î±-naphthaleneacetic acid on the number of responding explant, number of multiple shoot produced and length of the shoots were tested. after six weeks of culture, the percentage of responding shoot apices was highest on media supplemented with 1.5mg/L BAP with and without 0.1mg/L NAA.The number of responding apices decreasing with decrease in the concentration of BAP. Maximum number of multiple shoots  and the highest mean shoot length were also obtained when MS was supplemented with 1.5mg/L BAP with  and  without  0.1mg/L NAA.
Keywords: Tissue Culture, Organogenesis, Somatic Embryogenesis